Significance of Arbuscular Mycorrhizal Fungi in Mitigating Abiotic Environmental Stress in Medicinal and Aromatic Plants: A Review - Abir Israel; Julien Langrand; Joël Fontaine; Anissa Lounès-Hadj Sahraoui (Foods, 2022)
Medicinal and aromatic plants (MAPs) have been used worldwide for thousands of years and play a critical role in traditional medicines, cosmetics, and food industries. In recent years, the cultivation of MAPs has become of great interest worldwide due to the increased demand for natural products, in particular essential oils (EOs). Climate change has exacerbated the effects of abiotic stresses on the growth, productivity, and quality of MAPs. Hence, there is a need for eco-friendly agricultural strategies to enhance plant growth and productivity. Among the adaptive strategies used by MAPs to cope with the adverse effects of abiotic stresses including water stress, salinity, pollution, etc., their association with beneficial microorganisms such as arbuscular mycorrhizal fungi (AMF) can improve MAPs’ tolerance to these stresses. The current review (1) summarizes the effect of major abiotic stresses on MAPs’ growth and yield, and the composition of EOs distilled from MAP species; (2) reports the mechanisms through which AMF root colonization can trigger the response of MAPs to abiotic stresses at morphological, physiological, and molecular levels; (3) discusses the contribution and synergistic effects of AMF and other amendments (e.g., plant growth-promoting bacteria, organic or inorganic amendments) on MAPs’ growth and yield, and the composition of distilled EOs in stressed environments. In conclusion, several perspectives are suggested to promote future investigations.